Kajian Sosiolinguistik Pada Nama Aktivitas Masyarakat Solo Raya Dan Implementasi Dalam Pembelajaran Bahasa Indonesia - Deemuleh, Miss Nusreeyah, Drs. Agus Budi Wahyudi,M.Hum (2016)
This research is a qualitative descriptive study. The object of research is the name of community activity on the page Solopos Solo Raya newspaper. The purpose of this study, there are three first, to describe a form of community activity name in Solo Raya. Secondly, describes the meaning of the activity in the name of Solo Raya and third, describe the implementation of the nature and meaning of the name of Solo Raya community activities in learning Indonesian. Mechanical ably semuka informant interviews, recording technique, the technique used to obtain data noted in this study. After the data collected this study using a unified method of data analysis techniques, basic techniques of power pilah determining element, engineering refrensial frontier. The results of this study are the four things, (1) The form of the name of Solo Raya community activities. (2) Code languages on behalf of Solo Raya activity that is based on the origin of language in the form of community activity name contains Indonesian, English, Javanese, and mixed-language, English Indonesian. (3) The origin of the name of community activities Solo Raya there are five origin of the name of community activities Solo Raya (a) the name of community activity that shows the events or activities, (b) the name of community activities that show the culture, (c) the name of community activities that showed in place (d) the name of the activity which refers to the history and culture, and (e) the name of the historic activity. (4) Implementation of the nature and meaning of the name of community activities Solo Raya in the Indonesian language learning this study based on the syllabus berkurikulum 2013, RPP centralize KD: 4.1 Interpret the meaning of the text of historical stories, news, advertising, editorial/opinion, and novel either orally and in writing, indicators 4.1.1 Finding the meaning of a text message, both orally and in writing. Keywords: Study of Sociolinguistics, name of community activities, learning Indonesian